The Warren Buffett way workbook - Hagstrom, Robert G. 1956-; Rhoads, Russell (Wiley, 2013)
Warren Buffett Way Workbook consists of over 500 questions and answers to help readers of The Warren Buffett Way reinforce and cement their knowledge of Buffett's hugely successful investment approach. The Workbook follows The Warren Buffett Way, 3e, providing a combination of multiple choice and essay questions for each chapter in the core book. Given the depth and range of questions, a reader who masters the material in the Workbook will be equipped with the knowledge to begin to apply Buffett's methods to his/her own investment portfolio. All answers are provided in the Workbook, including answers to the essay questions. The perfect accompaniment to The Warren Buffett Way, 3e and The Warren Buffett Way Video Course, the Workbook will provide readers with a sure path to begin investing just like Warren Buffett.
Print version record
Keywords: Buffett, Warren; Capitalists and financiers -- Biography -- United States; Investments -- United States; Investissements; États-Unis; BUSINESS & ECONOMICS; Finance; Capitalists and financiers; Investments; United States; Biographies